2001
DOI: 10.1046/j.1440-1819.2001.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ricketts analysis and Downs‐Northwestern analysis for the evaluation of obstructive sleep apnea cephalograms

Abstract: To determine which analysis is suitable to examine the dentofacial skeletal pattern characteristics of the obstructive sleep apnea syndrome (OSAS), we took lateral cephalograms of 44 Japanese OSAS patients and 34 Japanese non-OSAS controls. By Ricketts analysis, we found significant differences between OSAS patients and non-OSAS controls on facial axis, lower facial height and total facial height, which showed that Japanese OSAS patients have dolico facial patterns. However, by Downs-Northwestern analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Analyses of lateral cephalograms of male Japanese OSA patients and non-OSA using Ricketts method indicated that the facial patterns of OSA patients are dolico, where the hyoid bone is positioned low, the soft palate is longer and the width of the airway is narrower than that of the non-OSA controls (7). In contrast, Downs-Northwestern analysis can not detect significant differences between Japanese OSA patients and non-OSA controls (19). The facial pattern with a downward mandible development, characteristic of OSA patients, is confirmed in another comparison study (20).…”
Section: Discussionmentioning
confidence: 80%
“…Analyses of lateral cephalograms of male Japanese OSA patients and non-OSA using Ricketts method indicated that the facial patterns of OSA patients are dolico, where the hyoid bone is positioned low, the soft palate is longer and the width of the airway is narrower than that of the non-OSA controls (7). In contrast, Downs-Northwestern analysis can not detect significant differences between Japanese OSA patients and non-OSA controls (19). The facial pattern with a downward mandible development, characteristic of OSA patients, is confirmed in another comparison study (20).…”
Section: Discussionmentioning
confidence: 80%
“…We selected some parameters not only from the Downs–North–Western analysis, but also from the Rikett's analysis. The facial axis can be used to estimate the facial length 28,29 . While the mean value of the facial axis in normal Caucasian subjects is 90°, the mean value is 86° in Japanese patients, 30 which means that the Japanese are a long‐faced race in comparison with Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…However, we [47] analyzed cephalograms of OSA patients and controls by Ricketts analysis and Downs-Northwestern analysis. We found out through Ricketts analysis that OSA patients had a Dolico facial pattern (increased anterior facial height) and a tendency to have a retropositioned mandible, long soft palate, decreased airway space, and lowered position of the hyoid bone.…”
Section: Craniofacial Pattern Of Osamentioning
confidence: 99%